Medical management of male infertility: now and future. Issue 1 (3rd January 2023) - Chen, Grace; Kathrins, Martin; Ohlander, Samuel; Niederberger, Craig
Abstract : Purpose of review: Medical therapy for idiopathic male infertility has historically been empiric and based on small observational studies rather than larger well designed clinical trials. This review is timely and relevant because of the recent publication of several studies that are less susceptible to bias because of being placebo-controlled and more highly powered. Recent findings: The largest proportion of recent publications covered antioxidants, with eight randomized controlled trials (RCTs) included in this review. The Males, Antioxidants, and Infertility (MOXI) trial is of particular interest, being a large multicenter RCT, which demonstrated no improvement in semen parameters or live-birth rates with antioxidant use. In addition, phosphodiesterase-5 inhibitors (PDE5i) have been shown to improve semen parameters, while duloxetine use was not associated with any adverse effects on sperm. Progress was also made in the realm of regenerative medicine, with the realization of the first successful primate model of sperm production from pluripotent stem cells. Summary: It may be time to stop recommending antioxidants for idiopathic male infertility given recent studies suggesting lack of efficacy, but given their relative safety, it is reasonable to continue their use until the evidence is overwhelming. Otherwise, stem cell therapy is another anticipated area of research interest.